1996
DOI: 10.1046/j.1365-2443.1996.27029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe mra1 gene, which is required for cell growth and mating, can suppress the mating inefficiency caused by a deficit in the Ras1 activity

Abstract: Background: Schizosaccharomyces pombe Ras1 regulates two downstream pathways, namely the Byr2/Byr1/ Spk1 mitogen-activated protein kinase cascade and the Cdc42sp small G protein pathway. The former is relevant to mating and sporulation, whereas the latter is relevant to mating, cell growth and cell morphology. We addressed whether Ras1 has any additional role in the regulation of cell physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…A previous study of the fission yeast orthologue of Emg1, called Mra1, suggested that Mra1 might genetically interact with the Ras-signaling pathway, because overexpression of mra1 suppressed an allelic ras1 mutation that resulted in inefficient mating (Hakuno et al, 1996). Epistasis experiments, however, indicated that Mra1 suppression of the rasS40T allele was indirect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study of the fission yeast orthologue of Emg1, called Mra1, suggested that Mra1 might genetically interact with the Ras-signaling pathway, because overexpression of mra1 suppressed an allelic ras1 mutation that resulted in inefficient mating (Hakuno et al, 1996). Epistasis experiments, however, indicated that Mra1 suppression of the rasS40T allele was indirect.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature-sensitive allele of EMG1 was created based on the observation that a point mutation in the conserved central region of the Schizosaccharomyces pombe mra1 (K213E) led to a protein of altered function (Hakuno et al, 1996). An oligonucleotide (5Ј-ATA-GACCTGGACCN(C,G,T) TCCGGCTTTGTTGATTGG-3Ј) in which the first two positions of the homologous amino acid (K109) in baker's yeast EMG1 were randomized and a primer corresponding to the promoter of EMG1, we amplified the 5Ј-end of the EMG1 gene with the use of error-prone PCR.…”
Section: Generation Of Conditional Alleles Of Emg1 and Nop14mentioning
confidence: 99%
See 2 more Smart Citations
“…Cells of the ras1 deletion mutant are short and fat, in addition to being sterile, suggesting that they are defective in the maintenance of cell morphology (Fukui et al, 1986). Two pathways have been established to function downstream of Ras1p, although evidence suggesting a third possible pathway exists (Hakuno et al, 1996). One of the two is a MAP kinase cascade that transmits the mating pheromone signal and regulates nuclear gene expression, which is essential for mating but not for the maintenance of cell morphology (Wang et al, 1991;Nielsen et al, 1992;Xu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%